Hyperoxia/Hypoxia Exposure Primes a Sustained Pro-Inflammatory Profile of Preterm Infant Macrophages Upon LPS Stimulation - Twisselmann, Nele; Pagel, Julia; Künstner, Axel; Weckmann, Markus; Hartz, Annika; Glaser, Kirsten; Hilgendorff, Anne; Göpel, Wolfgang; Busch, Hauke; Herting, Egbert; Weinberg, Jason B.; Härtel, Christoph (Frontiers in Immunology, 2021)
Preterm infants are highly susceptible to sustained lung inflammation, which may be triggered by exposure to multiple environmental cues such as supplemental oxygen (O2) and infections. We hypothesized that dysregulated macrophage (MФ) activation is a key feature leading to inflammation-mediated development of bronchopulmonary dysplasia (BPD) in preterm infants. Therefore, we aimed to determine age-dependent differences in immune responses of monocyte-derived MФ comparing cord blood samples derived from preterm (n=14) and term (n=19) infants as well as peripheral blood samples from healthy adults (n=17) after lipopolysaccharide (LPS) exposure. Compared to term and adult MФ, LPS-stimulated preterm MФ showed an enhanced and sustained pro-inflammatory immune response determined by transcriptome analysis, cytokine release inducing a RORC upregulation due to T cell polarization of neonatal T cells, and TLR4 surface expression. In addition, a double-hit model was developed to study pulmonary relevant exposure factors by priming MФ with hyperoxia (O2 = 65%) or hypoxia (O2 = 3%) followed by lipopolysaccharide (LPS, 100ng/ml). When primed by 65% O2, subsequent LPS stimulation in preterm MФ led to an exaggerated pro-inflammatory response (e.g. increased HLA-DR expression and cytokine release) compared to LPS stimulation alone. Both, exposure to 65% or 3% O2 together with subsequent LPS stimulation, resulted in an exaggerated pro-inflammatory response of preterm MФ determined by transcriptome analysis. Downregulation of two major transcriptional factors, early growth response gene (Egr)-2 and growth factor independence 1 (Gfi1), were identified to play a role in the exaggerated pro-inflammatory response of preterm MФ to LPS insult after priming with 65% or 3% O2. Preterm MФ responses to LPS and hyperoxia/hypoxia suggest their involvement in excessive inflammation due to age-dependent differences, potentially mediated by downregulation of Egr2 and Gfi1 in the developing lung.